Gerenciamento de resíduos sólidos na UNESP Sorocaba - Nogueira, Lucas Augusto Silva [UNESP]; Sá, Alessandra Botignon de [UNESP]; Oliveira, Sabrini Santana de [UNESP]; Malatesta, Ana Carolina [UNESP]; Mancini, Sandro Donnini [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The modern society is struggling with a large solid waste the awareness, management and proper disposal are attitudes that seem to be the way to reduce and even solve this problem. As the university knowledge dissemination center is essential that serve as an example and to produce knowledge in this area. The Collectors is a project that connects the university and society producing knowledge and bringing education to students who are citizens in the future and bring changes in the university so that it can become an example. To realize this purpose the project works with proper disposal of solid waste including organic as described in this article campus of Sorocaba UNESP.

A sociedade atual enfrenta dificuldades com uma grande produção de resíduos sólidos e por isso a concientização, gerenciamento e destinação adequada são atitudes que parecem ser o caminho para diminuir e até solucionar este problema. Como a universidade tem função na sociedade como um centro de difusão de conhecimento, é fundamental que sirva de exemplo e que produza conhecimento nesta área. O Coletores é um projeto que faz a ligação entre a universidade e a sociedade produzindo conhecimento e trazendo educação aos universitários que serão os cidadãos no futuro, além de trazer transformações na universidade para que possa se tornar um exemplo. Para realizar este proposito o projeto trabalha com destinação adequada dos resíduos sólidos incluindo os orgânico.
Keywords: Environmental education; University; Solid waste; Educação ambiental; Universidade; Resíduos sólidos